Localization and evidences focused in the determination to Cerro Colorado IOCG deposit, Ancash-Peru - Torres Guerra, Alberto (2020)
This publication is part of the project: “Study of Mesozoic magmatism and its implications in the determination of a geological-structural exploration model related to the occurrence of IOCG type deposits in the Cordillera de la Costa and pre-Andean plains of the Peruvian Andes” by means of the framework agreement between UNMSM and INGEMMET. The location of the prospective areas was using Landsat 8 images, choosing Cerro Colorado Chico for its accessibility. The geomorphology stands out for showing outcrops of isolated hills with strong oxidation and hills. In the field stage, the geological cartography of 5 predefined zones and oriented sampling was performed. Intrusive rocks, altered porphyritic volcanic rocks, gaps, quartz veins, clays were observed. The mineralization observed was chalcopyrite, covelite, large amount of pyrite, hematite, goethite, jarosite, etc. The alteration observed was of strong silicification, oxidation, sericitation, chloritization and piritization. The results of the petromineralogical studies have determined the presence of rutile, micas, argillization and incipient carbonation. The presence of siliceous gaps without much obvious mineralization, found in Zone C-2, could indicate the presence of a possible Quartz Pod, in addition to having a large hematite-goethite halo, it could indicate a supergenous alteration and a lower temperature zone (due to the presence of the halo of quartz-hematite-sericite-chlorite alteration), giving the possible presence of magnetite in depth. Based on these evidences, the existence of an IOCG Type deposit in Zone C-2 is proposed, probably deep that, with more focused studies, this hypothesis would be corroborated.